(untitled) (Scientific journal of the Fergana State University, 2025)
The article analyzes the specific feature of art - artistic images. In this, in particular, the main attention is paid to the images of plants. In the lyrical form, the expression of the artistic view of the world is carried out by means of different forms of the image. Among them, the most actively used images belong to the world of flora. The genesis of floristic images in artistic creation goes back to ancient times. Man exists in unity with society, nature and universe. From this point of view, it is appropriate to describe it in a state of juxtaposition among the objects and phenomena of nature and existence. After all, it is necessary to emphasize that a unique poetics of expressing the artistic view of the world through floristic images has been formed in the new Uzbek poetry. The purpose of this study is to determine the characteristics of these principles. In the article, comparative-historical, comparative-typological, linguistic, and analytical methods of analysis were used in researching the issue of artistry and poetics of the image of plants in modern lyrics. As a result, the artistic significance of plant images used in new Uzbek poetry is highlighted. In the example of the poems of a number of artists, attention is focused on the symbolic and symbolic content expressed by them. Consequently, it is based on the fact that the way of understanding the floristic world has changed, and the way of active use of plant images in its artistic expression is also based.